Quality of life and associated factors of heroin‐dependent patients receiving methadone and buprenorphine maintenance treatment - Hu‐Ming Chang; Ming‐Chyi Huang; Su‐Chen Fang; Shih‐Ku Lin (Wiley, 2023)
Abstract Aim Although studies in Western countries have investigated the quality of life (QoL) of heroin users, limited research on this topic has been conducted in Asia. The present study assessed QoL in patients with heroin dependence receiving medications to treat opioid use disorder. Methods We performed a cross‐sectional study of patients with heroin dependence receiving methadone and buprenorphine treatment. The demographic and substance use variables of patients receiving methadone and buprenorphine were compared. The Chinese Health Questionnaire (CHQ‐12), Obsessive Compulsive Drug Use Scale (OCDUS), and World Health Organization Quality of Life Short Form Taiwan version (WHOQOL‐BREF‐T) were administered to measure patient mental health problems, addiction severity, and QoL, respectively. Multivariate regression was used to identify the factors associated with QoL. Results A total of 149 patients receiving methadone and 31 receiving buprenorphine completed the questionnaires. Individuals in the buprenorphine group were more likely to be married (p = 0.024) or employed (p = 0.024), have a higher educational level (p = 0.013), have lower drug craving (OCDUS: p = 0.035), or have higher QoL (WHOQOL‐BREF‐T: p = 0.004) than those in the methadone group. After adjustment for other variables, employment was positively associated with the physical, psychological, and environmental domains of QoL. Receiving buprenorphine treatment (p = 0.032) and longer treatment duration (p = 0.016) were associated with higher psychological QoL. Conclusion Several factors were associated with QoL in patients with heroin dependence. Some measures may improve their QoL, such as reducing employment barriers, improving treatment adherence, or increasing accessibility to buprenorphine treatment.